Polemik Usia Hewan Aqiqah: Studi Komparasi Pendapat Imam Madzhab Hukum Islam (UINSI Samarinda, 2017)
This article seeks to explore about the normative age of animals sacrificed in the aqiqah process. Aqiqah is Islamic terminology which signifies the sacrifice of an animal on the occasion of a child's birth. This normative study is based on the phenomenon of the sacredness of the aqiqah process that every economically capable parent is required to do. Several questions arise related to the phenomenon: is the type and age of animals sacrificed for aqiqah equal to the sacrificial animal requirements slaughtered on the day idul adha? How did the jurists of the Islamic school of law base their arguments on the age of aqiqah animal? The study finds that there is hardly any fundamental difference from classical scholars about the age of aqiqah animals. The results of this study confirm that animals can be slaughtered as aqiqah when it reaches the age of al-tsaniy/tsaniyah/musinnah except for sheep which is sufficient with the age of al-jadza’/jadza’ah. Nevertheless, some Islamic jurists, though a minority, say that aqiqah animals slaughtered below the age are still valid and counted as rewards for the parents.Keywords: Islamic law, aqiqah in Islam, age of animals sacrificed in the aqiqah, al-tsaniy and al-jadza’